A saga of administrative thought in presidential rhetoric an analysis of the state fthe nation addresses and speeches of Philippine presidents, 1935-2006 - Almase, Ananda Devi Domingo; Reyes, Danilo R. (2007)
Vita.
Thesis (D. Public Administration)--University of the Philippines, Diliman.
Keywords: Presidents -- Philippines -- Messages; Philippines -- Politics and government